Fostering EFL Learners' Digital Empathy through Multimodal Composing. (April 2020) - Jiang, Lianjiang; Gao, Jinyuan
The emergent cyber-violence along with the omnipresence of digital media has made the development of English as a Foreign Language (EFL) learners' digital empathy a shared concern among contemporary language educators. Yet how this could be done in EFL/ second language (L2) pedagogies remains underexplored. Informed by a conceptualization of digital empathy as 'cognitive and emotional ability to be reflective and socially responsible while strategically using digital media', this study reports on a study that explores whether and how digital empathy can be fostered through a pedagogic innovation that engages students with digital multimodal composing (DMC) of videos in their conventional English curriculum. Aligning with a DMC approach to literacy through which learners were encouraged to construct meanings by drawing on multiple modes from their everyday media experiences, this study took place in a secondary English classroom at a vocational school in China. Data from interviews, observations and student-authored videos and documents showed that the DMC process enhanced students' awareness of having more empathy when engaging with online activities. The findings also show that with such enhanced awareness, students learned to use digital technologies for resolving important social issues and then became more active and responsible participants online. Implications about using DMC as an approach to develop students' digital empathy in the mainstream English curriculum are also discussed.